A comprehensive characterization of membrane vesicles released by autophagic human endothelial cells. Issue 7 (5th April 2013) - Pallet, Nicolas; Sirois, Isabelle; Bell, Christina; Hanafi, Laïla‐Aïcha; Hamelin, Katia; Dieudé, Mélanie; Rondeau, Christiane; Thibault, Pierre; Desjardins, Michel; Hebert, Marie‐Josée
Abstract : The stress status of the apoptotic cell can promote phenotypic changes that have important consequences on the immunogenicity of the dying cell. Autophagy is one of the biological processes activated in response to a stressful condition. It is an important mediator of intercellular communications, both by regulating the unconventional secretion of molecules, including interleukin 1β, and by regulating the extracellular release of ATP from early stage apoptotic cells. Additionally, autophagic components can be released in a caspase‐dependent manner by serum‐starved human endothelial cells that have engaged apoptotic and autophagic processes. The nature and the components of the extracellular vesicles released by dying autophagic cells are not known. In this study, we have identified extracellular membrane vesicles that are released by human endothelial cells undergoing apoptosis and autophagy, and characterized their biochemical, ultrastructural, morphological properties as well as their proteome. These extracellular vesicles differ from classical apoptotic bodies because they do not contain nucleus components and are released independently of Rho‐associated, coiled‐coil containing protein kinase 1 activation. Instead, they are enriched with autophagosomes and mitochondria and convey various danger signals, including ATP, suggesting that they could be involved in the modulation of innate immunity.